A utilização das tecnologias assistidas por computador como elemento de integração, pesquisa e desenvolvimento nas disciplinas de projeto para a engenharia e design - Hellmeister, Luiz Antonio Vasques [UNESP]; Deganutti, Roberto [UNESP]; Palhaci, Maria do Carmo Jampaulo Plácido [UNESP]; Hellmeister, Victor (My University, 2011)
The use of technologies called computedassisted, such as CAD - (Computed Aided Design), CAM - (Computed Aided Manufacturing) and CNC - (Computed Numerical Control), increasingly demanded by the market, are needed in the teaching of subjects technical drawing and design courses for engineering and design. However its use findl barriers in the more conservative wing of the academy, who advocate the use of traditional drawing, for the settling of the concepts and the development of spatial reasoning. This study aimed to show the results obtained with the design and production of an apparatus for measuring a three-dimensional computer-aided milling machine, interaction, integration and consolidation of concepts, fully demonstrating that the learning of computer-assisted technology is possible, and its use is most appropriate, meaningful and productive, than the use of instruments in the classic design.
Keywords: Computed assited technologies; CAD; CAM; CNC